Rise to the occasion: The trajectory of a novice Japanese teacher's first online teaching through action research - Chen, Cheng Chiang; Eriko, Sato (SAGE, 2019)
Foreign language teaching in distance education is administratively and pedagogically challenging; research on the perspectives of novice practitioners’ online teaching is also relatively scarce. This study explores how a novice Japanese teacher navigated and negotiated her professional development in a two-way virtual practitionership during her first online teaching. Data were collected from ongoing dialogue journals between the novice and her mentor followed by a semi-structured interview. Qualitative results indicate that pedagogically-sound and personalized digital tools can not only reduce the psychological distance between the teachers and students, but facilitate online teaching and learning via a performance-driven, standard-based curriculum. Informed by Action Research, the study reveals how both practitioners de/reconstructed their teacher identities and achieved professional empowerment through robust supervision and reciprocal teacher evaluation in a virtual environment. It further demonstrates the extent to which this evidence-driven and research-oriented approach can better address the genuine concerns of a foreign language program in distance education. Specifically, this context-responsive study indicates the improvement of online course delivery, teacher training and program sustainability in its own right.